2008
DOI: 10.1038/nn2048
|View full text |Cite
|
Sign up to set email alerts
|

Control of visually guided behavior by distinct populations of spinal projection neurons

Abstract: A basic question in the field of motor control is how different actions are represented by activity in spinal projection neurons. We used a new behavioral assay to identify visual stimuli that specifically drive basic motor patterns in zebrafish. These stimuli evoked consistent patterns of neural activity in the neurons projecting to the spinal cord, which we could map throughout the entire population using in vivo two-photon calcium imaging. We found that stimuli that drive distinct behaviors activated distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
275
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(297 citation statements)
references
References 46 publications
22
275
0
Order By: Relevance
“…In another study, two-photon calcium imaging identified specific spinal projection neurons whose activity correlate with stimuli evoking turns. Subsequent femtosecond laser ablation of a small subset of those neurons eliminates turning toward the ablated side, confirming the subset as a necessary component of the turning circuitry [137]. A recent study also imaged microscopic flow in developing embryos by using femtosecond laser ablation to generate fluorescent debris [138].…”
Section: Zebrafishmentioning
confidence: 85%
“…In another study, two-photon calcium imaging identified specific spinal projection neurons whose activity correlate with stimuli evoking turns. Subsequent femtosecond laser ablation of a small subset of those neurons eliminates turning toward the ablated side, confirming the subset as a necessary component of the turning circuitry [137]. A recent study also imaged microscopic flow in developing embryos by using femtosecond laser ablation to generate fluorescent debris [138].…”
Section: Zebrafishmentioning
confidence: 85%
“…Although assessments of zebrafish retinal and/or tectal networks versus reticular and/or spinal networks are usually performed independently, more recent work has begun to bridge the visual and motor control fields. For example, drifting gratings have been used to reveal the reticulospinal circuitry responsible for asymmetric movements (Orger et al, 2008), to confirm the cerebellum's role in processing discrepancies between perceived and expected sensory feedback (Ahrens et al, 2012) and to implicate the dorsal raphe in different states of arousal (Yokogawa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Subpopulations of RSNs located in discrete brainstem regions are recruited in the control of different components of sensorimotor integration (Dampney, 1994;UllĂ©n et al, 1997;Orlovsky et al, 1999;Fagerstedt et al, 2001;Yeomans et al, 2002;Dubuc et al, 2008). In teleost fish, lesion experiments and imaging of neuronal activity suggest that subpopulations of RSNs in midbrain and hindbrain are important for control of visual prey capture (Gahtan et al, 2005), fast escape (see below), and optomotor response (Orger et al, 2008).…”
Section: Introductionmentioning
confidence: 99%